Strategy for Imidazotetrazine Prodrugs with Anticancer Activity Independent of MGMT and MMR - Garelnabi, Elrashied A. E; Pletsas, Dimitrios; Li, Li; Kiakos, Konstantinos; Karodia, Nazira; Hartley, John A; Phillips, Roger M; Wheelhouse, Richard T (ACS medicinal chemistry letters, 2012)
The imidazotetrazine ring is an acid-stable precursor and prodrug of highly reactive alkyl diazonium ions. We have shown that this reactivity can be managed productively in an aqueous system for the generation of aziridinium ions with 96% efficiency. The new compounds are potent DNA alkylators and have antitumor activity independent of the O6-methylguanine-DNA methyltransferase and DNA mismatch repair constraints that limit the use of Temozolomide.